2021
DOI: 10.1016/j.abd.2020.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged luteal phase support with progesterone may increase papules and plaques of pregnancy frequency in pregnancies through in vitro fertilization

Abstract: Background Pruritic urticarial papules and plaques of pregnancy development may have a strong relationship with hormone treatments during in vitro fertilization and hormonal changes during pregnancy. Objectives The aim of this study was to evaluate and compare the frequency of papules and plaques of pregnancy and related factors in in vitro fertilization pregnancies and spontaneous pregnancies. Methods In this study, 517 in vitro fertilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The intramuscular injections of synthetic progesterone for three weeks during her initial cycle of in vitro fertilization-embryo transfer were notably associated with photosensitivity localized in a vitiliginous facial lesion in a specific case [79]. Moreover, in a comprehensive case-control study, after a comparative analysis of single pregnancies, it was established that the incidence of pruritic urticarial papules and plaques of pregnancy (PUPPP) was significantly higher in individuals undergoing in vitro fertilization [80]. Notably, among IVF patients with PUPPP, there was a notable increase in both the duration of luteal-phase support with progesterone and the frequency of multiple pregnancies compared with IVF patients without PUPPP (p < 0.001 for both factors) [80].…”
Section: Progesterone Hypersensitivity and Its Impact On Fertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The intramuscular injections of synthetic progesterone for three weeks during her initial cycle of in vitro fertilization-embryo transfer were notably associated with photosensitivity localized in a vitiliginous facial lesion in a specific case [79]. Moreover, in a comprehensive case-control study, after a comparative analysis of single pregnancies, it was established that the incidence of pruritic urticarial papules and plaques of pregnancy (PUPPP) was significantly higher in individuals undergoing in vitro fertilization [80]. Notably, among IVF patients with PUPPP, there was a notable increase in both the duration of luteal-phase support with progesterone and the frequency of multiple pregnancies compared with IVF patients without PUPPP (p < 0.001 for both factors) [80].…”
Section: Progesterone Hypersensitivity and Its Impact On Fertilitymentioning
confidence: 99%
“…Moreover, in a comprehensive case-control study, after a comparative analysis of single pregnancies, it was established that the incidence of pruritic urticarial papules and plaques of pregnancy (PUPPP) was significantly higher in individuals undergoing in vitro fertilization [80]. Notably, among IVF patients with PUPPP, there was a notable increase in both the duration of luteal-phase support with progesterone and the frequency of multiple pregnancies compared with IVF patients without PUPPP (p < 0.001 for both factors) [80]. Furthermore, PUPPP has been previously linked with increased progesterone receptor immunoreactivity and multiple pregnancy-induced high progesterone levels [81,82].…”
Section: Progesterone Hypersensitivity and Its Impact On Fertilitymentioning
confidence: 99%
“…A study of 517 in vitro fertilization (IVF) pregnancies and 1,253 spontaneous pregnancies concluded that PEP was statistically more frequent in pregnancies resulting from IVF than in spontaneous pregnancies. Also, it was suggested that prolonged treatment with progesterone might be related to a higher frequency of PEP 19 .…”
Section: Polymorphic Eruption Of Pregnancymentioning
confidence: 99%
“…Correctly applied suture contributes to accelerating the healing process, thereby reducing scarring in the affected areas and reducing the recovery period and postoperative complications (6). Although new studies have reported possible risks (12), especially related to scar defect of cesarean section, there is no suture method comparison for isthmocele, which is one of the cesarean scar defects (13,14). The surgical method used during the closure of the incision to be made to the uterus increases and decreases the probability of occurrence of complications such as isthmocele, rupture, location, and invasion anomalies (15,16).…”
Section: Introductionmentioning
confidence: 99%